The PHQ-2 on OASIS-C: A New Resource for Identifying Geriatric Depression Among Home Health Patients - Sheeran, Thomas (2010)
Since Medicare first implemented the home care Outcome and Assessment Information Set (OASIS) in 1999, we have learned a great deal about depression among the homebound elderly. First, we know that major depression is a highly prevalent illness in home care. With depression rates at almost 15%, home care—along with nursing homes—has among the highest rates of any healthcare setting (Bruce et al., 2002; Parmelee et al., 1992; Jones et al., 2003).